2020
DOI: 10.1111/jgh.15328
|View full text |Cite
|
Sign up to set email alerts
|

Features associated with high‐risk sessile serrated polyps at index and follow‐up colonoscopy

Abstract: Background and Aim Clinically significant serrated polyps are precursors of colorectal cancers, with features considered high risk including size ≥10 mm, dysplasia, and presence of synchronous conventional adenoma. While these features have been described in cohorts undergoing screening colonoscopy, there is little information regarding the prevalence and patient characteristics associated with high‐risk sessile serrated polyps (SSPs) in those undergoing surveillance colonoscopy. Methods Polyp pathology at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Existing data revealed age as a risk factor for SSLs. Anwar et al ( 38 ) reported that age ≥ 75 years was independently associated with advanced SSLs. The progression of SSLs to dysplasia and even to CRC is accelerated due to age-related methylation and synergizes with CIMP ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing data revealed age as a risk factor for SSLs. Anwar et al ( 38 ) reported that age ≥ 75 years was independently associated with advanced SSLs. The progression of SSLs to dysplasia and even to CRC is accelerated due to age-related methylation and synergizes with CIMP ( 39 ).…”
Section: Discussionmentioning
confidence: 99%